Dietary magnesium deficiency induces the expression of neuroinflammation‐related genes in mouse brain. Issue 2 (6th March 2021) - Tsuji, Ryuhei; Inoue, Hirofumi; Uehara, Mariko; Kida, Satoshi
Abstract: Aims: Dietary Mg 2+ deficiency (MgD) impairs hippocampus‐dependent memory in mice; however, the molecular mechanisms underlying MgD‐induced memory impairments are unclear. Here, we investigated the molecular signatures in the hippocampus of MgD mice by analyzing the hippocampal transcriptome. Methods: We performed RNA‐sequencing of the hippocampal transcriptome of MgD mice. We used gene ontology analyses and quantitative real‐time PCR to validate the RNA‐sequencing results. Results: mRNAs for neuroinflammation‐related genes were upregulated in the hippocampus and cortex of MgD mice. Conclusion: MgD induces neuroinflammation in the mouse brain, including the hippocampus and cortex. Our findings suggest that MgD‐induced neuroinflammation triggers the impairments of hippocampus‐dependent memory. Abstract : This study aimed to identify the molecular signatures of dietary Mg 2+ deficits (MgD) ‐induced deficits of hippocampus‐dependent memory performance in mice by analyzing the hippocampal transcriptome. MgD mice exhibited that mRNAs for neuroinflammation‐related genes were upregulated in the hippocampus and cortex, suggesting that MgD induces neuroinflammation in the mouse brain. Our findings suggest that MgD‐induced neuroinflammation triggers the memory impairments.